IS Strategic Planning of GBI SOKID using Enterprise Architecture Planning and Risk Management ISO 31000:2018 - Riyanto, Joseph Alan; Tambotoh, Johan Jimmy Charter (Sistemasi: Jurnal Sistem Informasi, 2024)
In the midst of the massive and rampant that use in every sector of our life makes Information System is needed. Back then, to entry data in a sector was did mannualy which they had to write it down into books, this thing would create any mistake, data redudancy, or perhaps the book would gone. Therefore, Information system would be necessary whether for company or organization. Gereja Bethel Indonesia Sokaraja Kidul (GBI SOKID) is a church which haven’t using information system in their daily operational activity. Thus, this system is aim to help GBI SOKID to optimalized and increasing value-added from their daily operational activities. This Information System Strategic Planning is using Enterprise Architecture Planning as a method to create some of architectures which will be proposed and also create implementation planning. Beside of it, this research also adding Risk Management using ISO 31000:2018 to map some risks would be come up and also solutions are being proposed. The results form this research are Portofolio of GBI SOKID’s Information System and risk map, risk evaluation, also solutions that will be proposed.